Synthesis of silica nanoparticles for the functionalization of textiles - Guevara Moreno, Ana Milena
Silica particles were obtained by the Stöber method, in order to analyze the feasibility of creating a pedagogical guide that allows apprentices to apply knowledge about nanotechnology for the functionalization of textiles. The assembly of the reactor was carried out with the instruments and equipment of the laboratory of the Textile and Leather Manufacturing Center, and, through a video, the reaction step by step was documented.According to the factorial experimental design, nine experiments were carried out, with two control variables: reaction time with the catalyst (0.5 hours, 1 hour and 2 hours) and quantity of the catalyst NH4OH at 30% (15%, 20% and 25 %). The samples were analyzed by SEM microscopy, finding that, with 1 hour and 20% of the catalyst, more uniform and smaller particles were obtained, while with 0.5 hours and 2 hours, the particles were more amorphous. Through the nanosizer particle size analyzer, it was obtained that the average is 349.5nm with a high dispersion. The product obtained has potential for use in fabrics as a waterproofing, self-cleaning and anti-puncture agent, since the particle size is small enough to be incorporated into thick fibers.It was concluded that during the process, it is essential to maintain constant agitation at 190 RPM and increase to a minimum of 400 RPM in the addition of the catalyst. It is recommended to analyze how the order of addition of the reagents and the synthesis of particles at ambient conditions influence the final size.